Life‐history traits correlate with temporal trends in freshwater fish populations for common European species. (7th November 2020) - Santos, Raphaël; Poulet, Nicolas; Besnard, Aurélien
Abstract: Understanding the population dynamics of aquatic species and how inter‐specific variation in demographic and life history traits influence population dynamics is crucial to define their conservation status and design appropriate protection measures. The abundance and biomass growth rates for 18 common European freshwater fish species were estimated using data spanning 1990–2011 for 546 sites across France. Fish‐length trends were assessed using quantile regressions and correlations with life history traits were investigated. Amongst the 18 species, eleven of them have exhibited a significant decline in abundance and 14 species declined in biomass, seven remained stable or exhibited positive abundance growth rates; for four species, biomass was stable or increased. Of the demographic and ecological traits investigated, life‐history strategy and maximum length were significantly correlated with species' population growth rates, revealing that the decline mainly concerned large‐bodied species with slow life‐histories. These results focus on 18 common European species representing 94% of fish captured during the study period within the French national monitoring programme and underline that more attention should be paid to the decline in common species. Population dynamics of widely distributed common species are key drivers of communities and of importance to ecosystem function. This study provides evidence of declines in common European freshwater fish species at a national scale and recommends conservation measures to favour recovery of most declining species. We highlight the crucial value of electrofishing monitoring programmes to assess freshwater fish species population trajectories and to support environmental management and conservation policy based on scientific evidences.